Imaging prior to radiotherapy impacts in-vitro survival. (October 2020) - Kench, Peter L.; Rogers, Linda; Esteves, Ana; Gorjiara, Tina; Mackonis, Elizabeth Claridge; Morrell, Stephen; McKenzie, David R.; Suchowerska, Natalka
Abstract: Background and purpose: Cone Beam Computed Tomography (CBCT) is routinely used in radiotherapy to identify the position of the target volume. The aim of this study was to determine whether the CBCT dose, when followed by the treatment, influences the therapeutic outcomes as determined by in-vitro clonogenic cell survival in a radiobiological experiment. Materials and methods: Human cell lines, four cancer and one normal, were exposed to a 6 MV photon beam, produced by a linear accelerator. For half of each sample, a prior imaging dose was delivered using the on-board CBCT. A sample size of n = 103 was used to achieve statistical power. Results: The experimental group of cell lines exposed to CBCT imaging prior to treatment exhibited a reduction in mean cancer cell survival of ~17 times (p = 0.02) greater than predicted from the average dose response and equivalent to more than 5% of the therapeutic dose, compared to 11 times greater than predicted for normal cells (n.s.). Conclusion: The greater than predicted reduction in survival resulting from the additional CBCT dose is consistent with radiation-induced bystander effects.